2012
DOI: 10.3109/13697137.2012.656160
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-related genes and postmenopausal osteoporosis risk

Abstract: Variants of the new candidate genes (NRIP and BMP15) can predispose patients to osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In particular, women with an activating FSHR N 680 S polymorphism have an increased risk of developing postmenopausal osteoporosis, independent of circulating levels of FSH and estrogens (52). Likewise, in a multicenter study of postmenopausal Spanish women two-gene combinations of wild type IVS4 or 3′UTR markers of CYP19A1 with FSHR and BMP15 genes yielded skeletal protection (53). Therefore, epidemiologic data derived from several cross-sectional and cohort studies, together with genetic association studies, suggest a detrimental effect of FSH on bone.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, women with an activating FSHR N 680 S polymorphism have an increased risk of developing postmenopausal osteoporosis, independent of circulating levels of FSH and estrogens (52). Likewise, in a multicenter study of postmenopausal Spanish women two-gene combinations of wild type IVS4 or 3′UTR markers of CYP19A1 with FSHR and BMP15 genes yielded skeletal protection (53). Therefore, epidemiologic data derived from several cross-sectional and cohort studies, together with genetic association studies, suggest a detrimental effect of FSH on bone.…”
Section: Introductionmentioning
confidence: 99%
“…Like sex, genetic traits are nonmodifiable factors for osteoporosis 19 and approximately 75% of osteoporosis is heritable. 21 Moreover, BMD, an essential biomarker for osteoporosis and osteoporotic fracture prediction is a highly heritable quantitative trait. 7 , 10 , 22 It is evident that approximately 50% to 82% of variations in BMD are of genetic origin.…”
mentioning
confidence: 99%
“…The single-nucleotide polymorphisms (SNPs) of the NRIP1 gene which modulates transcriptional activity of the oestrogen receptor, were correlative with postmenopausal osteoporosis. 36,37 Chen and Xia 38 showed that there was a close relationship between NRIP1 and BMD in B cells in a microarray study. The expression of IRAK3 is predominantly in peripheral blood leukocytes and induced strongly upon the maturation of macrophages.…”
Section: Discussionmentioning
confidence: 99%